Effectiveness of the complex treatment of idiopathic scoliosis in children. Pair controlled investigation - Pugacheva, N. V (Pohybové ústrojí. Pokroky ve výzkumu, diagnostice a terapii, 2013)
A pair controlled investigation for effectiveness of complex conservative treatment of idiopathic scoliosis to be evaluated was performed in patients matched by sex and severity and pattern of the deformity. 38 patients of the therapeutic group and the same quantity of the control one were examined at the clinic of the center. During 6 weeks all the patients were conservatively treated with therapeutic program developed by specialists of our center including therapeutic exercises, apparatus physiotherapy with electric, magnetic and light therapy techniques and also procedures of functional bioregulation with videocomputer auto training and electromyographic feed back and Chêneau brace. Patients of the therapeutic group had corrective exercises according to Schroth method in H. R. Weiss’ modification additionally. Effectiveness of treatment evaluated with instrumental diagnostic techniques: computer optical topography, stabilometry and spirometry. Positive results of the study confirm that application of this complex conservative treatment (during 6 weeks) in children with scoliosis combined with Schroth-Weiss exercises allow to achieve obvious deformity correction and reduce symptoms of the disease.
Keywords: dechová terapie; Female; kombinovaná terapie; techniky fyzikální terapie; skolióza; výsledek terapie; ženské pohlaví; Spirometry; Adolescent; Schroth-Weiss cvičení; lidé; Physical Therapy Modalities; Exercise Therapy; studie případů a kontrol; Treatment Outcome; Vital Capacity; vitální kapacita; Kyphosis; Case-Control Studies; Combined Modality Therapy; Scoliosis; Respiratory Therapy; terapie cvičením; spirometrie; mladiství; kyfóza; Humans